Applied Mathematical Modelling and Heat Transport Investigation in Hybrid Nanofluids under the Impact of Thermal Radiation: Numerical Analysis. (21st December 2021) - Khan, Umar; Ullah, Basharat; Khan, Wahid; Adnan,; Khan, Ilyas; Fayz-Al-Asad, Md.
Abstract : Nanofluids are solid-liquid mixtures that have a dispersion of nanometer-sized particles in conventional base fluids. The flow and heat transmission in an unstable mixed convection boundary layer are affected by the thermal conductivity and dynamic viscosity uncertainty of a nanofluid over a stretching vertical surface. There is time-dependent stretching velocity and surface temperature instability in both the flow and temperature fields. It is possible to scale the governing partial differential equations and then solve them using ordinary differential equations. Cu and Al2 O3 nanofluids based on water are among the possibilities being investigated. An extensive discussion has been done on relevant parameters such as the unsteadiness parameter and the mixed convection parameter's effect on solid volume fraction of nanoparticles. In addition, alternative nanofluid models based on distinct thermal conductivity and dynamic viscosity formulas are examined for their flow and heat transmission properties. On the basis of the comparison, it is concluded that the results are spot on for steady state flow.